Hubungan Pengetahuan Ibu tentang ASI Eksklusif dengan Praktik Pemberian ASI pada Bayi - Nurul Hidayah; Najla Fazila Windra; Izmi Raditya Putri; Rani Suraya (Jurnal Sains Farmasi Dan Kesehatan, 2025)
This study aims to analyze the relationship between mothers' knowledge of exclusive breastfeeding and their breastfeeding practices, as well as identify supporting and inhibiting factors in its implementation in Mekar Sari Village, Deli Serdang Regency. The research employed a descriptive quantitative method with 30 mothers of infants aged 0–6 months selected through purposive sampling. Data were collected through interviews using structured questionnaires. The results revealed that the majority of mothers (93.3%) practiced exclusive breastfeeding, though challenges such as perceived insufficient milk supply (50%) and the introduction of complementary foods before six months (53.3%) persisted. Adequate maternal knowledge, family support (96.7%), and information from healthcare workers (96.7%) were identified as critical factors for successful exclusive breastfeeding. These findings underscore the need for continuous education, family support, and breastfeeding-friendly workplace policies to improve exclusive breastfeeding rates and support optimal infant health.